Respuesta :
(x^2-3x+2)-1(3x^2-5x-1)=
x^2-3x+2-3x^2+5x+1=
x^2-3x^2-3x+5x+2+1=
-2x^2+2x+3
x^2-3x+2-3x^2+5x+1=
x^2-3x^2-3x+5x+2+1=
-2x^2+2x+3
(x² - 3x + 2) - (3x² - 5x - 1)
This problem can be split up into like terms. So, all of the terms containing x² would be put together, the terms containing just one x would be put together, and the terms without x's would be put together.
(x² - 3x²) = -2x²
(-3x - -5x) Simplify the double negative
(-3x + 5x) = 2x
(2 - -1) Simplify the double negative
(2 + 1) = 3
So, when you put those all together you get -2x² + 2x + 3.
This problem can be split up into like terms. So, all of the terms containing x² would be put together, the terms containing just one x would be put together, and the terms without x's would be put together.
(x² - 3x²) = -2x²
(-3x - -5x) Simplify the double negative
(-3x + 5x) = 2x
(2 - -1) Simplify the double negative
(2 + 1) = 3
So, when you put those all together you get -2x² + 2x + 3.